Profound softening and shear-induced melting of diamond under extreme conditions: An ab-initio molecular dynamics study. (December 2019) - Wen, Libin; Wu, Hao; Sun, Hong; Chen, Changfeng
Abstract: Diamond retains original crystal form and large elastic stiffness up to very high temperatures, and strengthens considerably under high pressures. These remarkable characters dictate its behaviors under extreme loadings such as those in laser-heated diamond anvil cells (LHDACs) or giant planetary interiors. Here we report surprising findings from ab initio molecular dynamics simulations revealing that diamond's mechanical strengths reduce precipitously at elevated temperatures, by 50% at 3000 K, despite that its elastic parameters remain little changed. Our results also unravel an extraordinary shear-induced reduction of melting temperature of diamond under ( 111 ) [ 11 2 ¯ ] shear strains by as much as 1150 K, greatly altering its pressure-temperature ( p − T ) phase diagram when shear deformations exist. These new benchmarks offer crucial insights for elucidating extreme mechanics of diamond at high p - T conditions, advancing fundamental knowledge with major implications for LHDAC operation and planetary modeling. Graphical abstract: Image 1